Controlled depolymerisation, as assessed by analytical ultracentrifugation, of low molecular weight chitosan for potential use in archaeological conservation - Wakefield, Jennifer M.K.; Gillis, Richard B.; Adams, Gary G.; McQueen, Caitlin; Harding, Stephen E. (Springer, 2018)
The heterogeneity and molecular weight of a chitosan of low molecular weight (molar mass) and low degree of acetylation (0.1), for potential use as a consolidant for decayed archaeological wood, has been examined by sedimentation velocity and sedimentation equilibriumin the analytical ultracentrifuge before and after depolymerisation. Sedimentation velocity before polymerisation revealed a uniform distribution of sedimentation coefficient with little concentration dependence. SEDFIT-MSTAR analysis revealed a weight average molecular weight Mw of (14.2 + 1.2) kDa, and polydispersity index of ~ 1.2. Further analysis using MULTISIG revealed a distribution of material between 2-20 kDa and consistent with the weight average Mw. Controlled depolymerisation using hydrogen peroxide and UV in an acetic acid medium reduced this to (4.9 + 0.7) kDa, with a similar polydispersity. The depolymerised material appears to be within the range that has been predicted to fully penetrate into archaeological wood. The consequences for this and the use of the analytical ultracentrifuge in wood conservation strategies is considered.